2000
DOI: 10.1111/j.1447-0756.2000.tb01192.x
|View full text |Cite
|
Sign up to set email alerts
|

New Method to Prevent Bladder Dysfunction after Radical Hysterectomy for Uterine Cervical Cancer

Abstract: The new method significantly reduces bladder dysfunction after radical hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 10 publications
0
32
1
4
Order By: Relevance
“…Rob was the first with a review in Lancet Oncology [3]. His paper is of main interest because it summarizes the anatomy and the differ- [20] 1987 article case-control prospective 13 5 -x low Hockel [21] 2000 article case-control prospective* 41 139…”
Section: Discussionmentioning
confidence: 99%
“…Rob was the first with a review in Lancet Oncology [3]. His paper is of main interest because it summarizes the anatomy and the differ- [20] 1987 article case-control prospective 13 5 -x low Hockel [21] 2000 article case-control prospective* 41 139…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, surgical techniques could be used to separate the bladder branches of the pelvic nerves by isolating a thin membranous layer containing the nerves from the lateral surface of the posterior layer of the vesicouterine ligament [20]. Thereafter, the posterior layer of the vesicouterine ligament was dissected.…”
Section: Isolation or Recognition Of The Bladder Branches Of Pelvic Nmentioning
confidence: 99%
“…The former can then be safely clamped, cut, and ligated without damaging the hypogastric nerves or the proximal part of the pelvic nerve plexus. The problem of sparing autonomic nerves to the bladder in the vesicouterine ligament has been addressed by Kuwabara et al [20]. Intraoperative electrical stimulation of various parts of the vesicouterine ligament and the simultaneous measurement of intravesical pressure identified that the lateral layer of the posterior part of the vesicouterine ligament was the major pathway of the bladder branches of pelvic nerves.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for preserving these nerves during surgery is to avoid the well-known sequelae of nerve damage, such as impaired bladder function [2], rectal motility disorders and sexual dysfunction [3][4][5]. Our nerve-sparing surgical technique was based on extensive cadaver studies [6] and the experience of Japanese surgeons [7,8], and an approach was chosen to make the technique applicable for Western patients with a higher mean body mass index (BMI) and different disposition of fat in the pelvis as compared to Asian women. Our proposal was not an entirely new form of radical hysterectomy but, rather, the description of individual nerve-sparing steps that could be incorporated into any particular type of radical hysterectomy.…”
Section: Introductionmentioning
confidence: 99%